2020
DOI: 10.1016/j.omtn.2020.09.041
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-221 Inhibits Latent TGF-β1 Activation through Targeting Thrombospondin-1 to Attenuate Kidney Failure-Induced Cardiac Fibrosis

Abstract: Kidney failure (KF) is associated with cardiac fibrosis and significantly increased mortality in heart failure. Thrombospondin-1 (TSP1), a key regulator of latent transforming growth factor-β1 (L-TGF-β1) activation, is a predicted target of miR-221. We hypothesized miR-221 attenuates severe KF-associated cardiac fibrosis via targeting of Thbs1 with subsequent inhibition of L-TGF-β1 activation. Rat cardiac fibroblasts (cFB) were isolated and transfected with microRNA-221 (miR-221) mimics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…To sum up, downregulated miR-221 might promote LF hypertrophy through inducing collagens I and III expression via targeting TIMP-2. A growing body of evidence showed that miR-221 was one of fibrosis-associated miRNAs and played important parts in the occurrence and development of fibrotic diseases, such as liver fibrosis (Tsay et al, 2019), cardiac fibrosis (Zhou et al, 2020), and renal fibrosis (Morinaga et al, 2016). Therefore, future researches are expected to conduct a further exploration of miR-221 as the potential therapeutic target for HLF.…”
Section: Mir-221mentioning
confidence: 99%
“…To sum up, downregulated miR-221 might promote LF hypertrophy through inducing collagens I and III expression via targeting TIMP-2. A growing body of evidence showed that miR-221 was one of fibrosis-associated miRNAs and played important parts in the occurrence and development of fibrotic diseases, such as liver fibrosis (Tsay et al, 2019), cardiac fibrosis (Zhou et al, 2020), and renal fibrosis (Morinaga et al, 2016). Therefore, future researches are expected to conduct a further exploration of miR-221 as the potential therapeutic target for HLF.…”
Section: Mir-221mentioning
confidence: 99%
“…Procter et al [ 22 ] also found platelet hyperaggregability, induced by the release of TSP-1 from platelet α-granules, may diminish nitric oxide signaling, thus promoting inflammation. Recently, Zhou et al [ 23 ] reported that microRNA-221 could inhibit latent TGF-β1 activation by targeting TSP-1 to attenuate cardiac fibrosis, which could be a possible upstream treatment of AA.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al (114) proved that miR-221 inhibits the activation of L-TGF-β1 by directly targeting THBS1, thus mitigating cardiac fibrosis and improving cardiac function. Similarly, miR-221 mimics transfected into rat cardiac fibroblasts induced by kidney failure resulted in reduction of cardiac fibrosis.…”
Section: Mir-221mentioning
confidence: 99%
“…Similarly, miR-221 mimics transfected into rat cardiac fibroblasts induced by kidney failure resulted in reduction of cardiac fibrosis. Therefore, miR-221 mimics are a promising therapeutic target in cardiac fibrosis (114).…”
Section: Mir-221mentioning
confidence: 99%